Clinical evaluation of the ICare tonometer in measuring intraocular pressure - Krzyżanowska-Berkowska, Patrycja; Asejczyk-Widlicka, Magdalena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To compare the intraocular pressure (IOP), values obtained with the ICare rebound tonometer with the Goldmann applanation tonometer (GAT), and to evaluate the influence of central corneal thickness (CCT), and radius of the corneal curvature (R) on IOP measurements. Material and methods: Eighty four eyes of 48 subjects (65 eyes of glaucoma patients and 19 eyes of healthy volunteers), were examined with ICare and Goldmann tonometers. Central corneal thickness was determined by ultrasound pachymetry. Corneal radius of curvature was determined using corneal topography. Results: There was no significant difference between IOP readings with ICare and GAT. Intraocular pressure measurements were found to be higher with the ICare tonometer, both in glaucoma patients (15.3 ± 4.0 mmHg), and normal subjects (14.4 ± 3.0 mmHg). ICare-GAT mean difference was 1.1 ± 3.6 mmHg (95% CI, -6.1-8.3 mmHg), for glaucoma patients and 1.8 ± 3.2 mmHg (95% CI, -4.6-8.2 mmHg), for healthy volunteers. Using CCT patients were divided into 2 groups: 1) thinnest corneas – CCT≤556 μm and 2), thickest corneas – CCT>556 μm. In the group of thinnest corneas there was no correlation between IOP, CCT and R. In thickest corneas there was significant correlation between IOP readings obtained by ICare and CCT (r = -0.4, p<0.01), and mean radius (R) (r = 0.5, p<0.001). Conclusions: Measurements of IOP using the ICare rebound tonometer are in good agreement with Goldmann applanation tonometer, although influenced by CCT.